Druggability assessment of precursor membrane protein as a target for inhibiting the Zika virus. Issue 8 (24th May 2022) - Mulgaonkar, Nirmitee; Wang, Haoqi; King, Maria; Fernando, Sandun
Abstract: The Zika virus (ZIKV), a significant zoonotic flavivirus, was neglected as a human pathogen until the recent epidemic. The rapid geographic spread of the virus and association with neurological disorders has created a global public health concern pressing the need for anti-ZIKV drugs. Previous ZIKV drug discovery research has focused on three primary targets, RNA-dependent RNA polymerase, envelope protein, and viral proteases, and none has yet resulted in a commercially viable inhibitor. In the quest for finding effective inhibitors, it is important to expand the number of targets available for drug discovery research. To this end, the ZIKV precursor membrane protein (prM) comes to the forefront as a potential target due to its critical role in virus infectivity and pathogenicity. prM acts as a chaperone for envelope protein folding and prevents premature fusion of virions to the host membrane and has not been attempted as a drug target before. One critical requirement for a protein to be an effective target is the ability of the protein to be druggable, i.e. having active sites that can bind to specific ligands. In this work, the druggability of prM was assessed via molecular docking combined molecular dynamics simulations followed binding affinity kinetics studies. Compounds that had a high affinity to the prM protein were screened in silico and ligand-binding free energies were computed using molecular mechanics with generalized Born and surface area continuum solvation (MM-GBSA) method. In vitro binding kinetics via biolayer interferometry (BLI) and interaction analysis confirmed that prM could be targeted for drug discovery to combat ZIKV infection. Communicated by Ramaswamy H. Sarma